Assessment of the Characteristics and Associated Factors of Infectious Complications in Bullous Pemphigoid - Chen, Jia; Mao, Xuming; Zhao, Wenling; Zhang, Bingjie; Chen, Xinyi; Yu, Chenyang; Zheng, Zehui; Jin, Hongzhong; Li, Li (Frontiers in Immunology, 2020)
Objectives The clinical outcome of bullous pemphigoid is worse in patients with infectious complications. Assessment of the prevalence and risk factors of infectious complications will be necessary to plan preventative strategies and to instruct the treatment plans. We sought to determine the risk factors of infection and compare associated factors in inpatients and outpatients with different system infections. Design This is a single-centered retrospective study on the medical records of 252 patients from 2010 to 2018 at the dermatology department, Peking Union Medical College. Patients’ medical profiles of medical history, diagnosis, infectious complications, and treatment plans were analyzed. The associated factors were compared between the subgroups, including inpatients and outpatients, different body sites of infection. Results Of the total 252 patients with bullous pemphigoid (BP), 81 patients (81/252, 32.1%) had infectious complications. Forty-eight patients died from pulmonary infections (11/48, 22.9%), cardiovascular diseases (6/48, 12.5%), and other diseases. Infections were most frequently found in skin/mucosa (44/252, 17.5%), respiratory system(32/252, 12.7%) and blood (10/252, 4.0%). On multivariate analysis, risk factors of infections in BP were maximal control dose of corticosteroids (OR 2.539, 95% CI 1.456-4.430, p = 0.001), low serum albumin level (OR 2.557, 95%CI 1.283, 5.092, p = 0.007), hospitalization (OR 4.025, 95%CI 2.289, 7.079, p < 0.001), comorbidities including respiratory disease (OR 4.060, 95%CI, 1.861, 8.858, p < 0.001)), eye disease (OR 4.431, 95%CI 1.864, 10.532, p < 0.001), and diabetes (OR 2.667, 95%CI 1.437, 4.949, p = 0.002). The rate of infection was significantly higher in inpatients compared to that in outpatients (54.0% vs. 20.6%, p < 0.001), with diverse risk factors. Mucocutaneous infections were associated with a maximal control dose of corticosteroid and other dermatoses. Respiratory infections were related to respiratory disease and old age, and hematologic infection was associated with low serum hemoglobin levels and mucosa involvement of BP. Both of them were associated with mucosa involvement and high titer anti-BP180 antibody. Conclusions Infectious complications of BP are common and are associated with mucosal involvement of bullous pemphigoid, more comorbidities, the higher dose of corticosteroids, and the lower level of serum albumin.